Accuracy Assessment of Smartphone-Based 2D Positioning: Checking ItsSuitability for Non-Survey Geospatial Applications - Edward Guma; Akoji Augustine Haruna; Ojonumi Felix Idoko; Abdulrasheed Salihu (Civil Engineering Dept, Balikpapan State Polytechnics, 2026)
This study explores the potential of smartphone-based 3rd order 2D surveying as a cost-effective alternative for mapping and geospatial data acquisition. Traditional surveying methods rely on expensive equipment, but smartphones offer a promising solution, leveraging their widespread availability and accessibility. The study evaluates the accuracy and reliability of smartphone-based 2D surveying techniques, focusing on environmental factors that impact accuracy. The research uses a Vivo Y04 smartphone with SW Maps and Geo++ RINEX Logger apps to collect data at seven control points in Lokoja, Nigeria. Results show that environmental factors like buildings, trees, and telecommunication masts significantly impact accuracy, with deviations ranging from 0.337m to 8.036m.Control points in open fields with good satellite geometry achieved deviations of less than 100cm, while those near obstacles showed larger discrepancies. The SW Maps app demonstrated more reliable results compared to Geo++ RINEX. A hybrid approach combining satellite surveying with traditional methods can help achieve accurate results. The study highlights the potential of smartphone-based surveying for small-scale projects, developing countries, or applications with limited budgets. However, careful planning and selection of survey locations are crucial to minimize errors. The findings have implications for urban planning, environmental monitoring, and infrastructure development, and suggest that smartphone-based 3rd order 2D positioning can be a viable alternative for geospatial data acquisition. By understanding the limitations and capabilities of smartphone-based surveying, professionals can leverage this technology to achieve accurate and reliable geospatial data. Further research is needed to optimize location-based services in urban settings and to investigate the impact of different smartphone models and surveying techniques on accuracy